ESMERALDA - ENERGIZANDO SUA LUZ - Neitzel, Larice Marciane; Pauleski, Rosecléia de Siqueira; Garlet, Vanessa Cristina Angieli; de Oliveira, Katerine Medino (Anais de Saúde Coletiva, 2023)
Saúde. Estética e cosmética. Longevidade e a qualidade de vida.